OC-088 Associations Between Microbiota, Colonic Volume and Transit During A Low Fodmap Diet. (17th August 2016) - Jalanka, J; Sloan, T; Major, G; Krishnasamy, S; Pritchard, S; Mulvenna, C; Lomer, M; Gowland, P; Spiller, R; ,
Abstract : Introduction: Ingestion of poorly digested carbohydrates can induce functional gastrointestinal symptoms, which may be relieved by a diet low in fermentable oligo-, di-, mono-saccharides and polyols (FODMAPs). How dietary changes alter intestinal microbiota and gut function remains unclear. This abstract reports changes in microbiota seen in a randomised controlled trial presented at DDW 2014 1 and associations with colonic volume (CV), transit and dietary oligofructose. Methods: All subjects (healthy adults) followed a low FODMAP diet for 7 days, supervised by a registered dietitian. They supplemented their diet with oligofructose (OF) or maltodextrin (MD) 7 g twice daily. CV and transit were assessed by magnetic resonance imaging pre- and post-intervention, as were fasting breath hydrogen(H2 ) and methane(CH4 ). Stool samples were collected before and after intervention for exploratory analysis of microbiota by 16 S Miseq sequencing. Results: 37 subjects (19 OF: 18 MD) completed the trial. All reported results were significant at corrected level p = 0.05 unless stated. At baseline the combined abundance of 3 bacterial genera - Bifidobacteria, Ruminococcus and Oscillospira - correlated positively with CV (r = 0.49) and transit time (r = 0.29, p < 0.1) while the levels of Faecalibacteria and Lachnospiraceae correlated negatively with CV (r = 0.57) and transit (r = 0.35). CV increased in both groups but changes in microbial composition were different. Relative abundance of Actinobacteria, predominantly Bifidobacterium, decreased in the MD + low FODMAP diet group while the relative abundance of Coprococcus, Oscillospira and uncultured Clostridia increased. Abundance of the latter two correlated with fasting breath CH4 . In contrast Bifidobacteria and breath H2 both increased in the OF + low FODMAP diet group while abundance of Lachnospiraceae decreased. Conclusion: Increase in Bifidobacteria and H2 confirm previous reports after OF or the low FODMAP diet. The increase in certain bacterial taxa after MD may result from polysaccharides included in the low FODMAP diet. Larger volumes were associated with specific bacteria but the mechanism is unclear. Future research should include assessment of volumes, transit and microbiota to provide new insights into the complex relationship between microbiology, physiology and therapy. Reference: 1 Major, et al . OC-114, DDF 2014. Disclosure of Interest: None Declared